2016
DOI: 10.4103/0972-0707.186452
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of conventional syringe irrigation, vibringe, and passive ultrasonic irrigation performed with different irrigation regimes in removing triple antibiotic paste from simulated root canal irregularities

Abstract: Background:This study evaluated the efficacy of a sonic device (Vibringe), passive ultrasonic irrigation (PUI), and conventional syringe irrigation (CSI) in the removal of triple antibiotic paste (TAP) from artificial standardized grooves in the apical and coronal thirds of a root canal.Materials and Methods:One-hundred eighteen root canals were prepared using the ProTaper system. The roots were split longitudinally, and a standardized groove was prepared in the apical and coronal parts of one segment. The gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
(35 reference statements)
0
8
0
1
Order By: Relevance
“…The published literatures showed that it is a proper disinfectant when used as an intracanal medicament. In addition, in vivo and in vitro studies have shown that this combination of three antibiotics is effective in eliminating endodontic pathogens ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…The published literatures showed that it is a proper disinfectant when used as an intracanal medicament. In addition, in vivo and in vitro studies have shown that this combination of three antibiotics is effective in eliminating endodontic pathogens ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical and chemical approaches, including but not limited to endodontic files, irrigant solutions, and intracanal medicaments associated or not with emerging technologies (e.g., passive ultrasonic irrigation and photoactivated-induced passive irrigation) (712), have been used in both mature and immature permanent teeth. More specifically, among the presently available options, triple antibiotic paste (TAP, an equal parts mixture [1 g/mL] involving metronidazole [MET], ciprofloxacin [CIP], and minocycline [MINO]), has been recommended prior to evoke bleeding in regenerative-based procedures (1316).…”
mentioning
confidence: 99%
“…Therefore, a 1.5% NaOCl solution was preferred as an irrigant in this study, and it was combined with 17% EDTA. A previous study showed that combining EDTA and NaOCl could more effectively remove TAP than either NaOCl or EDTA alone, especially from the apical third of the root canal (13).…”
Section: Discussionmentioning
confidence: 98%
“…Various techniques are used for TAP removal from root canals; however, none of them can completely remove it from the root canal (10,13). The recently introduced XP-endo finisher file (XPF) (FKG Dentaire SA, La Chaux-de-Fonds, Switzerland) is a unique instrument that promises an enhanced final cleaning, even in the irregularities of root canal systems, due to its enhanced flexibility and expansion capability up to 3 mm in diameter to touch to the canal walls in threedimensions (14).…”
Section: Introductionmentioning
confidence: 99%